Early Prediction in Acute Pancreatitis: the Contribution of Amylase and Lipase Levels in Peritoneal Fluid - Frossard, Jean Louis; Robert, John; Soravia, Claudio; Mensi, Noury; Magnin, Anne; Hadengue, Antoine; Rohner, Adrien; Morel, Philippe (JOP. Journal of the Pancreas, 2016)
Context Predicting the severity of acute pancreatitis early in the course of the disease is still difficult. Objective The value of amylase and lipase levels in serum and peritoneal fluid might be of value in predicting the course of acute pancreatitis. Design Prospective study. Patients One-hundred and sixty-seven patients with acute pancreatitis as confirmed by computed tomography scan within 24 hours of admission were studied. Main outcome measures Each patient was given an enzymatic score which reflected the predominance of serum or peritoneal levels of amylase and/or lipase. Enzymatic score was 0 if neither enzyme was predominant in the peritoneal fluid, 1 if amylase or lipase alone were predominant and 2 if both enzymes were predominant. The predictive value of the enzymatic score or computed tomography scan for a severe attack was determined. Results One-hundred and thirty-three attacks were graded as mild (79.6%) and 34 were considered as severe (20.4%). The frequency of severe acute pancreatitis significantly increased as the enzymatic score increased (5.4%, 12.5%, and 31.7% in 0, 1, and 2 enzymatic score patients, respectively; P<0.001). An enzymatic score greater than 0 predicted a severe outcome in 32 of 34 patients (sensitivity 94.1%, specificity 26.3%), whereas an enzymatic score of 2 predicted a severe attack in 26 of 34 patients (sensitivity 76.5%, specificity 57.9%). Edema on computed tomography scan was found in 97 of 129 mild attacks (specificity 75.2%) and necrosis in 25 of 33 severe attacks (sensitivity 75.8%), whereas all patients with severe attacks exhibited extrapancreatic acute fluid collection (sensitivity 100%, specificity 34.9%). Conclusions Peritoneal dialysis is less predictive and more cumbersome than a computed tomography scan in the early prediction of acute pancreatitis. Image: Ribbon diagram of human salivary alpha-amylase. (Wikimedia Commons)